Akreditasi sebagai Instrumen Manajemen Mutu dan Produktivitas Lembaga Pendidikan: Tinjauan Konseptual Berbasis Total Quality Management - Mellyana Vita Apriliyani; Moh. Bisri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to analyze the role of the accreditation system in improving the productivity of educational institutions from a strategic management perspective. Accreditation is positioned not only as an external quality assurance mechanism based on compliance with the National Education Standards (SNP), but also as a strategic instrument that drives continuous institutional performance improvement. Within the framework of strategic management, accreditation functions as a performance-based evaluation tool that systematically integrates planning, implementation, control, and quality improvement. This study uses a descriptive qualitative approach with a library research method through analysis of books, scientific articles, and education accreditation policy documents. The results of the study indicate that accreditation significantly contributes to increasing the productivity of educational institutions, reflected in the efficiency of resource management, improvement in learning quality, strengthening of institutional governance, and increased public trust. Conceptually, accreditation forms a strategic cycle that connects quality standards with institutional productivity through mechanisms of self-evaluation, external validation, and continuous improvement follow-up. These findings affirm that accreditation is not merely a tool for measuring administrative quality, but an integral part of institutional development strategy to build competitive excellence and the sustainability of educational organizations. Therefore, the effectiveness of accreditation is highly determined by its integration with the institution's strategic management, the strengthening of a quality culture, as well as the consistency of post-accreditation guidance to realize productive, adaptive, and competitive educational institutions.